Analisis Sumber Belajar Berbasis Laboratorium Lapangan dalam Pembelajaran Geografi - Triyan Subhiansyah; Siti Fadjarajani; Ruli As'ari (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2023)
Geography learning is very relevant outside the classroom by utilizing the environment. However, there are difficulties for teachers in applying learning outside the classroom due to a lack of knowledge of relevant locations as field learning resources, especially for geography learning. This research is intended to analyze the utilization of the potential of the Bantarujeg District, Majalengka Regency as a field-based learning resource for geography learning. The type of research used is descriptive qualitative with natural observation method. The results showed that in the Bantarujeg District, Majalengka Regency had the potential as a source of field learning for geography learning that teachers and students could use to support geography learning.